Targeting Shikimate Kinase Pathway of Acinetobacter baumannii: A Structure-Based Computational Approach to Identify Antibacterial Compounds - Aparna Shil; Most. Afrin Akter; Arafin Sultana; Sajal Kumar Halder; Mahbubul Kabir Himel (Journal of Tropical Medicine)
Acinetobacter baumannii (A. baumannii) is an opportunistic bacterium that has developed multidrug resistance (MDR) to most of today’s antibiotics, posing a significant risk to human health. Considering the fact that developing novel drugs is a time-consuming and expensive procedure, this research focuses on utilizing computational resources for repurposing antibacterial agents for A. baumannii. We targeted shikimate kinase, an essential enzyme in A. baumannii, that plays a significant role in the metabolic process. The basis for generating new therapeutic compounds is to inhibit the shikimate kinase and thereby targeting the shikimate pathway. Herein, 1941 drug-like compounds were investigated in different in silico techniques for assessing drug-likeness properties, ADMET (absorption, distribution, metabolism, excretion, and toxicity) profiling, binding affinity, and conformation analysis utilizing Autodock-vina and SwissDock. CHEMBL1237, CHEMBL1237119, CHEMBL2018096, and CHEMBL39167178 were determined as potential drug candidates for suppressing shikimate kinase protein. Molecular Dynamics Simulation (MDS) results for root mean square deviation, root mean square fluctuation, hydrogen bond, and gyration radius confirm the drug candidates’ molecular stability with the target protein. According to this study, CHEMBL1237 (Lisinopril) could be the most suitable candidate for A. baumannii. Our investigation suggests that the inhibitors of shikimate kinase could represent promising treatment options for A. baumannii. However, further in vitro and in vivo studies are necessary to validate the therapeutic potential of the suggested drug candidates.